2022
DOI: 10.3171/2021.10.jns211380
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing deep brain stimulation for the treatment of drug-resistant temporal lobe epilepsy: a pilot study

Abstract: OBJECTIVE The authors sought to determine the antiseizure effects of deep brain stimulation (DBS) of the parahippocampal cortex (PHC) for treatment of drug-resistant mesial temporal lobe epilepsy (MTLE). METHODS After a 3-month baseline period, 6 adult patients with drug-resistant MTLE and hippocampal sclerosis (HS) had stereoelectroencephalography (SEEG)–DBS electrodes implanted at the PHC for identification of the seizure onset zone (SOZ). Patients entered an 8-month, randomized, double-blind protocol for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…An observational study of 25 patients with temporal lobe epilepsy with bilateral ( n = 15 ) or unilateral ( n = 10) implants showed a 91% median seizure reduction for focal impaired awareness seizures [21 ▪ ]. Stimulation was provided continuously at 130 Hz, 300 μs pulse width, with a target of 3 V. Stimulation of the parahippocampus with similar stimulation settings (although with 1 min on, 4 min off) showed a greater than 50% seizure reduction at 12 months for three out of six patients [22].…”
Section: Stimulation Targetsmentioning
confidence: 99%
“…An observational study of 25 patients with temporal lobe epilepsy with bilateral ( n = 15 ) or unilateral ( n = 10) implants showed a 91% median seizure reduction for focal impaired awareness seizures [21 ▪ ]. Stimulation was provided continuously at 130 Hz, 300 μs pulse width, with a target of 3 V. Stimulation of the parahippocampus with similar stimulation settings (although with 1 min on, 4 min off) showed a greater than 50% seizure reduction at 12 months for three out of six patients [22].…”
Section: Stimulation Targetsmentioning
confidence: 99%
“…These observations paved the way for hippocampal DBS for TLE in the early 21st century [4] , [5] , [6] , [7] , [8] , [9] , [10] , [14] . Recent studies have also highlighted the active role of the subiculum and parahippocampal gyrus in the propagation of temporal lobe seizures [10] , [15] . Bondallaz et al conducted a study involving eight patients with refractory MTLE who underwent invasive recordings to place a permanent DBS lead near the ictal focus [7] .…”
Section: Discussionmentioning
confidence: 99%
“…The above mentioned clinical evidence suggests that the subiculum may be also involved in seizure propagation [9] , [10] , [13] , [14] . Moreover, not only subiculum but also the parahippocampal cortex may be targeted in patients with severe HS and MTLE [15] . In the largest study of hippocampal DBS for MTLE, Cukiert et al found no correlation between the locations of active contacts and seizure reduction [16] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 F] 28 has also been studied for measuring cortical thickness and neurons, traumatic brain injury, and disorders such as epilepsy, as well as investigating the relationship between age and hearing, stroke, cerebral palsy, psychosis, aversive, awareness, , and healthy . However, despite the advantages of [ 18 F] 28 over [ 11 C] 28 , its widespread use has been hampered by low RCY or unavailability of precursors .…”
Section: F- and 11c-labeled Pet Tracers Based On Anestheticsmentioning
confidence: 99%